Diminished Clostridium difficile toxin A sensitivity in newborn rabbit ileum is associated with decreased toxin A receptor. - Eglow, R (1992)
Human infants are relatively resistant to Clostridium difficile-associated diarrhea and colitis compared to adults. In that toxin A is the major cause of intestinal damage with this organism, we compared toxin A receptor binding and biological effects in newborn vs adult rabbit ileum. Purified toxin A (M(r) 308 kD) was labeled with tritium or biotin with full retention of biologic activity. Appearance of specific toxin A brush border (BB) binding was strongly age dependent with minimal [3H]toxin A specific binding at 2 and 5 d of life, followed by gradual increase in binding to reach adult levels at 90 d. Absence of toxin A binding sites in newborn and presence in adult rabbits was confirmed by immunohistochemical studies using biotinylated toxin A. Toxin A (50 ng to 20 micrograms/ml) inhibited protein synthesis in 90-d-old rabbit ileal loops in a dose-dependent fashion. In contrast, inhibition of protein synthesis in 5-d-old rabbit ileum occurred only at the highest toxin A doses (5 and 20 micrograms/ml) and at all doses tested was significantly less than the adult rabbit ileum. In addition, toxin A (5 micrograms/ml) caused severe mucosal damage in adult rabbit ileal explants but had no discernable morphologic effect on 5-d-old rabbit intestine. Our data indicate that newborn rabbit intestine lacks BB receptors for toxin A. The absence of the high-affinity BB receptor for toxin A in the newborn period may explain lack of biologic responsiveness to purified toxin, and the absence of disease in human infants infected with this pathogen.